Nurses' Self-report on the Infection Control Unit Activities and their Experience in the Hospital toward Nosocomial Infections in the Sulaimani Hospitals - Ramand Mohammed Haji; Dana Abdilmagid Abdilkarim; Salar Ibrahim Ali; Srwa Salih Mohammad (Hawler Medical University, 2020)
Background and objectives: Nurses can prevent the occurrence and transmission of nosocomial infections by following infection control measures such as wearing gloves and masks, using appropriate disinfection of skin and preventing accidental needle-stick injuries. This research aimed to evaluate the availability of hospital uniforms, personal protective equipment, and infection control activities at hospitals in Sulaimani in the Kurdistan Region of Iraq, and to examine nurses' experience of nosocomial infections. Methods and materials: A cross-sectional study was performed at 10 governmental hospitals during the period from 20th February to 28th September 2018. 525 nurses were selected as participants by a convenience sampling method. A self-administrated questionnaire was used to collect data, which were analysed using SPSS software. Results: The results showed that 268 nurses (51%) reported that their hospitals provided sufficient uniforms to all the medical staff and the majority of nurses, 444 respondents (84.6%) stated that they were responsible for cleaning their working uniforms. 441 nurses reported that they did not acquire a nosocomial infection, and 479 (91.2%) did not have an accident during their work in the hospital. 79.9% of the nurses (404) reported recapping syringe needles after the usage, and 98 (18.7%) gave a low rating to the infection control unit activity in their hospitals. Finally, more than half of nurses (330) representing 62.9% of the sample were vaccinated against nosocomial infections. Conclusions: Most of Sulaimani governmental hospitals are providing sufficient uniforms for the health staff, the majority of nurses were vaccinated against one or more nosocomial infections, and the majority of nurses do needle syringe recapping.